Joseph Benson Foraker papers - Foraker, Joseph Benson, 1846-1917.
Five volumes of correspondence pertaining chiefly to national politics and to the Republican Party. Correspondents include Marcus Alonzo Hanna, Theodore Roosevelt, John Sherman, and William H. Taft.
Printed volumes, in part.
Army officer, governor of Ohio, and U.S. senator from Ohio.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Republican Party (U.S. : 1854- ); United States -- Politics and government -- 1865-1933.; Army officers; Governors -- Ohio; Senators, U.S. Congress -- Ohio